COMUNICAÇÃO NO PONTO-DE-VENDA: ASPECTOS SENSORIAIS NA AMBIENTAÇÃO DAS MEGALIVRARIAS - Sá, Andréa Firmino de (2009)
This research aims to investigate and discuss the store layout as an element of communication applied to the point of sale book store, observing and analyzing how the current stores are being adapted to the market reality, which aims to provide the customer with a pleasant experience, considering the competition against e-commerce and supermarkets that have been selling books. It aims to understand the use of the different senses, which are: touch, smell, taste, sight and hearing in the point of sale itself. The object of study is Livraria Cultura, at Conjunto Nacional, since it s the biggest book store in Brazil, considering its dimensions. Since it s a contemporary phenomenon inside real life, the methodology is the Single Study Case and the methodology procedures are: direct observation of the customer at the point of sale, bibliography research and interviews with frequent customers and professionals in this area. We can conclude that the hedonistic characteristics of the contemporary customer, who searches for pleasant experiences associated to the synergy in integrated marketing communication, favors the positive results presented by the book store.(AU)